Anticonvulsants for chronic low-back pain - Bezerra, Dailson M. [UNESP]; El Dib, Regina [UNESP]; Vidal, Edison I.O. [UNESP]; De Barros, Guilherme A.M. [UNESP]; Chou, Roger; Fukushima, Fernanda [UNESP] (Wiley, 2014)
This is the protocol for a review and there is no abstract. The objectives are as follows: To assess the effectiveness and safety of anticonvulsants for the management of chronic low-back pain, with or without radiculopathy.